Research-Based Pocket Book as Fungi Learning Media - Lilis Supratman; Yamin Yamin (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
Fungi endophytic is microscopic so that the results of the documentation of the research can be documented in the form of a pocket. The book pocket is a media of learning that are practical and easy to carry anywhere. In this pocket-book, outlined that the fungi endophytic obtained on the organs of Ciplukan plants namely roots, stems and leaves. Fungi endophytic obtained four isolate suspected of having a substance compound antimicrobials against pathogenic bacteria. Test the feasibility of a pocket book to be used as a source of learning has been validated by experts learning media and material experts. Validation results show an average of 84.31% resulting in valid criteria. The validators statement based on validation states pocketbooks can be used as a source of learning.